Чудеса, да и только: [сказки] : (6+) / Наталья Абрамцева - Абрамцева Наталья Корнельевна (Сказка за сказкой, 2014)
Экземпляры: ф.9 (20151105) / Инвентарный номер: 059617 / Цена: 87.00 / Авт.знак: A16 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6